2018
DOI: 10.3390/ijms19040940
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a SBP-Box Gene (VpSBP16) from Chinese Wild Vitis Species in Arabidopsis Improves Salinity and Drought Stress Tolerance

Abstract: Salinity and drought are two major abiotic stresses that limit grape productivity. Responses to stress in grape are known to be regulated by several families of transcription factors. However, little is known about the role of grape Squamosa promoter binding protein (SBP)-box transcription factor genes in response to abiotic stress. To better understand the functions of the grape SBP-box genes in abiotic stress tolerance, a full-length complementary DNA (cDNA) sequence of the putative SBP-box transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…Squamosa promoter binding protein-like (SPL) is a key regulator of plant abiotic stress tolerance. VpSBP16 and BpSPL9 enhance salt and drought stress tolerance in Arabidopsis and Betula platyphylla, respectively [63,64], indicating that miR156 may also participate in the salt stress response in sweet potato. AP2 TFs have been reported to be regulated by miRNA172 and play an important role in the transcriptional regulation of biological processes involved in the growth and development and in the response to abiotic stress [65,66].…”
Section: Analysis Of Differential Mirnas In Response To Salt Stress Imentioning
confidence: 99%
“…Squamosa promoter binding protein-like (SPL) is a key regulator of plant abiotic stress tolerance. VpSBP16 and BpSPL9 enhance salt and drought stress tolerance in Arabidopsis and Betula platyphylla, respectively [63,64], indicating that miR156 may also participate in the salt stress response in sweet potato. AP2 TFs have been reported to be regulated by miRNA172 and play an important role in the transcriptional regulation of biological processes involved in the growth and development and in the response to abiotic stress [65,66].…”
Section: Analysis Of Differential Mirnas In Response To Salt Stress Imentioning
confidence: 99%
“…At present, the functions of SPL genes in more and more species has been unearthed: Grape VpSBP11 can regulate floral transition and leaf development [36]; BlSPLs in Betula luminifera interact with DELLA protein to participate gibberellin regulation [27]. It is reported that, except flowering, SPL genes are vital in also other physiological processes in plants, such as adventitious root development [13,37], fertility [38], fruit growth and quality [39], floral organ and shoot development [40,41], plant hormone response [42], morphological differentiation [43], and stresses response [44].…”
Section: Introductionmentioning
confidence: 99%
“…The grapevine variety Vitis yeshanensis was sampled from the eld, located in the grape germplasm resource garden of Northwest A&F University. Annual plants are selected for treatment, and the treatment method is the same [53]. Root samples were taken at 0d, 2d, 4d, 6d, 8d and 10d respectively for subsequent experiments.…”
Section: Plant Materialsmentioning
confidence: 99%
“…For chlorophyll content measurements, approximately 0.05 g of fresh leaf material was placed in 5 ml of 96% ethanol and incubated at 4•C in the dark overnight. The absorbance of the extracted pigments was measured at 665 and 649 nm using a spectrophotometer (Hitachi Limited, Tokyo, Japan) and the chlorophyll content was calculated as previously described [53].…”
Section: Physiological Analysis Of Drought Stress Response Of Transgementioning
confidence: 99%